Catholyte as an environmentally friendly detergent: effect on the colourfastness of black dyed textiles. Issue 10 (2nd October 2020) - Cronjé, Natasha; Steyn, Hester J. H.; Schall, Robert
ABSTRCT: Decreasing the impact of pollution caused by laundry detergents could be beneficial to the environment and global textile industry. Catholyte is electrochemically activated aqueous media which has no detrimental effects on water systems. Catholyte's pH and detergency properties remain in an altered state of metastability for 48 h, subsequently returning to its pre-activation state. The effect of Catholyte on appearance properties of dyed cotton was compared to non-phosphate detergent and evaluated. Laundering cotton with Catholyte caused slightly less colourfastness (sulphur and direct black), higher wash fastness (reactive black) and less staining (direct black). Using non-phosphate detergent resulted in less staining (sulphur and reactive black). The effects of Catholyte and detergent on the colourfastness to dry rubbing (sulphur, direct and reactive black) and colourfastness to wet rubbing (direct and reactive black) was similar. Catholyte has high potential as an environmentally friendly alternative to laundry detergents for sustainable consumption of cotton textiles.